Optimalisasi Nutrisi AB Mix dan Giberelin terhadap Pertumbuhan Vegetatif Melon Hidroponik Dutch Bucket - Muhammad Ilham; Asmah Indrawati; Saipul Sihotang (Universitas Medan Area, 2026)
The vegetative growth of melon (Cucumis melo L.) grown in hydroponic systems is influenced by proper nutrient management and the application of plant growth regulators. This study aimed to evaluate the effects of AB Mix nutrient concentration, gibberellic acid (GA₃), and their interaction on the vegetative growth of melon cultivated in a Dutch Bucket hydroponic system. The experiment was conducted at the CV. BestFarm Greenhouse, Deli Serdang Regency, North Sumatra, Indonesia, from December 2025 to March 2026 using a factorial Completely Randomized Design (CRD). The treatments consisted of three AB Mix concentrations (1800, 2200, and 2600 ppm) and four GA₃ concentrations (0, 40, 60, and 80 ppm). The results showed that AB Mix had a highly significant effect on several vegetative growth parameters, including plant height, number of leaves, leaf area, stem diameter, and vine length, with 2200 ppm producing the optimum vegetative growth. GA₃ application and its interaction with AB Mix had no significant effect on all observed vegetative growth parameters. These findings indicate that optimum AB Mix nutrition plays a more important role than GA₃ application in improving the vegetative growth of melon cultivated under a Dutch Bucket hydroponic system.